Pengaruh Negatif di Era Teknologi Informasi dan Komunikasi Pada Remaja (Perspektif Pendidikan Islam) - Kurnia, Lita; Edwar, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
The development of information and communication technology can no longer be avoided. Because with the information and communication technology, a person's life will feel easier. One can send messages easily, send and search for information quickly and easily. But behind these conveniences, it is necessary to pay attention to what are the negative impacts of information and communication technology on teenagers, especially teenagers today. In this era of information and communication technology, every effort and activity as well as deliberate action to achieve a goal must have the right foundation for a good and strong footing. Islamic religious education as an effort to shape human beings, must have a basis on which all activities and all formulation of the goals of Islamic education are linked. Islamic religious education in overcoming the negative influence of the era of information and communication technology on adolescents is the main educators for parents or the community who provide Islamic religious knowledge to adolescents so that they can fortify themselves in behaving, thinking, and acting in accordance with the provisions laid down. ordained by Allah SWT. for the safety of his life. According to the research title, this research is qualitative. Qualitative research is research that uses a natural setting in order to interpret phenomena that occur and is carried out with the intention of interpreting existing phenomena and is carried out by involving various existing methods, while the methods that are usually used are interviews, observation, and use of documents.